Sistem Pendukung Keputusan Penentuan Supplier Pembelian Barang Menggunakan Metode Analytical Hierarchy Process pada PT. Perintis Sarana Pancing Indonesia - Arjon Samuel Sitio (Journal Of Informatic Pelita Nusantara, 2017)
Technological advances are accelerating withinera of globalization in the business world, so as not to closethe possibility that a decision is madeis something that is very vital in determiningdecisions to be taken in the facecompetition in the business world. Decision-making caninfluenced by several aspects, this can beaffect the speed in making decisionsby a decision maker where decision-making should befast and accurate.This study was made usingAnalytical Hierarchy Process method. Where is the algorithmthis does the calculation process to searchthe best decision, that is by countingvalue criteria and compare it withthe calculation of each possible decisionwill be taken. This software will be used for divisionpurchasing assessment used is quality, product, price, and delivery.From the results of design and application testing. Decision Support System will generate a decisionthat is precise and flexible with that aspectinfluencethe decision, and producereports for users to understand the decisiontaken. Keywords: Analytical Hierarchy Process (AHP), Decision Support System, Supplier